Affective ecologies, adaptive management and restoration efforts in the Sacramento-San Joaquin Delta. Issue 9 (29th July 2019) - Kraus-Polk, Alejo; Milligan, Brett
Abstract : In this article, we describe ecological recovery efforts – restoration – as a crucial component of strategic delta planning. We present restoration as a design process at once biogeophysical and territorial that entails socioecological uncertainties. Adaptive management is an approach to dealing with uncertainties through active monitoring and recalibration of actions taken. We have developed a 'socioecological monitoring' program that uses existing biophysical monitoring protocols to collect data on human use. Beyond provisioning demographic and use data, this program also helps to change the relationship between the monitors and managers involved in adaptive management and diverse non-scientific publics, who have thus far been removed from the process. Our approach highlights the importance of user experiences and affective labor to bring people into the design of restoration areas, both as actors to be managed for, as well as agents whose values and desires can help guide landscape evolution.